Neolithic Shrine (The Biblical archaeology review, 2022)
While excavating ancient Neolithic hunting traps in Jordan’s southeastern desert near the site of Jibal al-Khashabiyeh, a team from the French Institute of the Near East and Jordan’s Al-Hussein Bin Talal University, co-directed by Wael Abu-Azizeh and Mohammad Tarawneh, made a unique discovery that sheds light on daily life and religious belief in the […]